Detection and Quantification of Viable but Non-culturable Campylobacter jejuni - Lv, Ruiling; Wang, Kaidi; Feng, Jinsong; Heeney, Dustin D.; Liu, Donghong; Lu, Xiaonan (Frontiers in Microbiology, 2020)
Campylobacter can enter a viable but non-culturable (VBNC) state to evade various stresses and this state is undetectable using traditional microbiological culturing techniques. These VBNC bacterial cells retain metabolism and demonstrate pathogenic potential due to their ability to resuscitate under favorable conditions. Rapid and accurate determination of VBNC Campylobacter is critical to further understand the induction and resuscitation of dormancy state of this microbe in the agri-food system. Here, we integrated propidium monoazide (PMA) with real-time polymerase chain reaction (qPCR) targeting the rpoB gene to detect and quantify C. jejuni in the VBNC state. First, we optimized the concentration of PMA (20 µM) that could significantly inhibit the amplification of dead cells by qPCR with no significant interference on the amplification of viable cell DNA. PMA-qPCR was highly specific to C. jejuni with a limit of detection (LOD) of 2.43 log CFU/mL in pure bacterial culture. A standard curve for C. jejuni cell concentrations was established with the correlation coefficient of 0.9999 at the linear range of 3.43 to 8.43 log CFU/mL. Induction of C. jejuni into the VBNC state by osmotic stress (i.e., 7% NaCl) was rapid (<48 h) and effective (>10% population). The LOD of PMA-qPCR for VBNC C. jejuni exogenously applied to chicken breasts was 3.12 log CFU/g. In conclusion, PMA-qPCR is a rapid, specific and sensitive method for the detection and quantification of VBNC C. jejuni in poultry products. This technique can give insight into the prevalence of VBNC Campylobacter in the environment and agri-food production system.